Research on Multi-Sensory Interaction Technology in Virtual Reality Environment - Li, Rui (Transactions on Computer Science and Intelligent Systems Research, 2024)
Multi-sensory interaction technology has a wide range of applications in virtual environments, covering a variety of fields such as urban planning, healthcare, education, etc., and demonstrating its potential for significant value in these fields. This paper reveals how multi-sensory interaction technology can enhance user immersion and interaction experience by simulating multiple sensory experiences through specific application cases. The purpose of this review is to integrate the research and applications of multi-sensory interaction technology in virtual environments from different fields in recent years. First, the paper details which sensory technologies have been integrated in different studies and what research results have been obtained from these studies. Moreover, the paper makes it clear that the sensory technologies most used in virtual environments are visual, auditory, and other sensory simulations. Although the sense of smell has begun to be utilized in some areas of research, it is still underdeveloped. As for taste interaction technology, it is still a relatively unexplored area in virtual environments. Most scholars mentioned in their research that with the continuous progress and maturity of technology, the application of multi-sensory interaction technology in virtual environments will be more extensive and in-depth. This will provide users with richer and more personalized experiences. This indicates that multi-sensory interaction technology has great potential for development in the future and will bring more innovation and change to virtual environments.